Nurturing care assets for food security: a community asset mapping approach - Gabriela Buccini; Kaelia Lynn Saniatan; Ana Poblacion; Ana Bauman; Cristina Hernandez; Cali Larrison; Dodds P. Simangan; Jyoti Desai; Yvonne Owens Ferguson; Alisa Howard; Melva Thompson-Robinson (BMC, 2024)
Abstract Background Zip codes classified by the Food Insecurity Index with moderate and high food insecurity (FI) risk can be a threat to the health and well-being of children during the first 1,000 days (from pregnancy to 2 years). The presence of nurturing care assets (i.e., stable environments that promote health and nutrition, learning opportunities, security and safety, and responsive relationships) can contribute to supporting families and their communities, and ultimately reduce systemic barriers to food security. We aimed to identify and characterize nurturing care assets in under-resourced communities with moderate and high FI risk. Methods Four steps were used to conduct a Community Asset Mapping (CAM): (1) review of community documents across five zip codes in Clark County, Nevada (2), engagement of community members in identifying community assets (3), definition of the assets providing nurturing care services, and (4) classification of assets to nurturing care components, i.e., good health, adequate nutrition, safety and security, opportunities for early learning, and responsive caregiving. The Food Insecurity Index was used to determine FI risk in each zip code. Analyses explored whether disparities in nurturing care assets across zip codes with moderate and high FI exist. Results We identified 353 nurturing care assets across zip codes. A more significant number of nurturing care assets were present in zip codes with high FI risk. The adequate nutrition component had the most assets overall (n = 218, 61.8%), while the responsive caregiving category had the least (n = 26, 7.4%). Most of the adequate nutrition resources consisted of convenience stores (n = 96), food pantries (n = 33), and grocery stores (n = 33). Disparities in the number and type of good health, early learning, and security and safety assets were identified within zip codes with high FI risk compared to moderate FI risk. Conclusions The quantity and type of nurturing care assets can exacerbate existing demographic disparities across zip codes, which are tied to barriers to access to food in under-resourced communities in Clark County, Nevada. Co-creating a nurturing care asset-based zip code strategy to address high FI risk will require strengthening systems across existing nurturing care assets.